The cry of the earth and the cry of the poor hearing justice in John's gospel - Rushton, Kathleen P. 1947- (London SCM Press, 2020)
"Despite the explicit proclamation in John's Gospel of the 'Word made flesh' it is hard to hear or preach such an esoteric Gospel in a way which offers something concrete, relevant and timely for congregations. Focused around the lectionary readings from the Gospel, "The Cry of the Earth and the Cry of the Poor" suggests that far from being a Gospel which sits at a safe remove from every day life, it can in fact be preached and read as an urgent call to hear the voices of the oppressed in our world. Encouraging preachers and those in the pews to engage in the ancient practice of lectio divina, the book offers an accessible resource to help address the divorce between what is heard from pulpit, and the urgent social and ecological justice concern of our times"--Back cover
Overview of the gospel of John -- Part 1. The Prologue -- From the beginnings to word made flesh : the Prologue: 1.1-5, 9-18 -- Part 2. The ministry of Jesus (1.19-12.50) -- Bethany across the Jordan : a man whose name was John: 1.6-8, 15, 19-34 -- Bethany across the Jordan : the first disciples of Jesus: 35-51 -- Cana : a wedding: 2.1-12 -- Jerusalem : Jesus in the Temple: 2.13-25 -- Jerusalem : a pharisee named Nicodemus: 3.1-21 -- Samaria : living water: 4.5-42 -- Jerusalem : cry of the marginalized: 5.1-47 -- Galilee : 'come, eat of my bread': 6.1-69 -- Jerusalem : 'rivers of living water': 7.37-39 -- Jerusalem : Jesus, the scribes, the pharisees and the woman: 8.1-11 -- Jerusalem : the beggar born blind: 9.1-41 -- Jerusalem : the good shepherd: 10.1-30 -- Bethany : Martha, Mary and Lazarus: 11.1-45 -- Bethany : Mary anoints Jesus: 12.1-8 -- Jerusalem : 'the hour' approaches: 12.12-16, 20-33 -- Part 3. The 'hour' of Jesus : the last night, passion and resurrection 13.1-21.25 -- Jerusalem : the last supper: 13.1-17.26 -- Jerusalem : Jesus washes feet: 13.1-17 -- Jerusalem : first part of the last supper discourse: 13.31-14.31 -- Jerusalem : second part of the last supper discourse: 15.1-16.4a -- Jerusalem : third part of the last supper discourse: 16.4b-15 -- Jerusalem : Jesus prays: 17.1-26 -- Jerusalem : the passion and death of Jesus: 18.1-19.42 -- Jerusalem : appearances of the risen Jesus: 20.1-31 -- Galilee : appearance of the risen Jesus to the seven disciples: 21.1-25 -- Appendix 1. Gospel of John : Sunday and main feasts liturgical year readings -- Appendix 2. Key words in the gospel of John.
New Zealand author
Includes bibliographical references (pages 218-225) and indexes
Keywords: Bible -- Commentaries; Bible -- Meditations; Bible; Justice -- Biblical teaching; Social Justice -- Religious aspects -- Christianity; Ecology -- Religious aspects -- Christianity; Christian Life; Vie chrétienne; Social justice - Religious aspects - Christianity; Ecology - Religious aspects - Christianity; Christian Life; Justice - Biblical teaching; Meditations; Commentaries